Evaluation of mechanical properties of jute fiber/carbon nano tube filler reinforced hybrid polymer composite. (2020) - Saiteja, J.; Jayakumar, V.; Bharathiraja, G.
Abstract: In present generation the use of natural fibres are increased highly in automobile sector as a potential renewable and eco-friendly materials. The natural fiber reinforced polymer composites are being presently used in various automobile industries as paneling elements in cars and in many internal parts. It can replace glass fiber reinforced plastics in many applications. This work focuses on dispersion of multi walled carbon nano tube in jute fiber and epoxy material. Five different proportions of multi walled carbon nano tube filler was taken (2%, 4%, 6%, 8%, 10%) to fabricate composite. The specimens were cut as per ASTM standard and the mechanical properties were evaluated as per ASTM testing methods. The results exhibited 3% volume nanotube composite has improved mechanical properties.